Common Bile Duct Obstruction by Free Floating Tumor. Issue 4 (1993) - Prinz, Richard A.; Ko, Tien C.; Maltz, Sheldon B.; Reynes, Carlos J.; Marsan, Richard E.; Freeark, Robert J.
Abstract : Tumors usually spread by local invasion or by vascular or lymphatic metastases. We report six patients in whom tumor cells were shed into the common bile duct with resulting obstruction. The three men and three women had jaundice and upper abdominal discomfort. Jaundice was intermittent in four patients. Preoperative total serum bilirubin ranged from 2.5 to 16.1 mg/dl; alkaline phosphatase ranged from 221 to 605 IU/1. Ultrsasound showed a dilated gallbladder [GB] in five patients with dilated intrahepatic ducts in three and stones in only one. ERCP showed a single filling defect in two of three patients and multiple defects in one. PTC showed multiple defects in one patient. At operation a thick gelatinous tissue fragment or clot was seen in the common bile duct of each patient. Frozen section identified tumor tissue in all. The source was GB carcinoma [2], GB adenomyoma [1], hepatic metastases of colon cancer [2] and common bile duct cancer [1]. Treatment consisted of pancreaticoduodenectomy [2], including one for GB cancer, left hepatic lobectomy [1], choledochoduodenostomy [1], common duct exploration with T-tube insertion and cholecystectomy [1]. One patient with metastatic colon cancer and another with gallbladder cancer died within one year of operation. The other four are alive from 2 to 4 years later. Conclusion: Benign or malignant tumors within the hepatobiliary tree can shed tissue into the common bile duct which can cause biliary obstruction. Any tissue fragment found in the common bile duct should be evaluated by frozen section. Recognition of this mode of tumor spread is needed for appropriate therapy of the underlying benign or malignant tumor.